Analysis of the Effectiveness of Using Digital Filters in Electronic Stethoscopes - Rohman, Andi Fathkur; Mak’ruf, Muhammad Ridha; Triwiyanto, Triwiyanto; Lamidi, Lamidi; Huynh, Phuoc-Hai (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The heart sound produced in some cases of the disease shows a certain pattern. The purpose of this study was to design an electronic stethoscope for cardiac auscultation with the following display. The contribution in this study is being able to show certain patterns that can be diagnosed in the sound signal. So that the pattern can be known when there is a heart disease disorder, an electronic stethoscope will be made for auscultation of the next display, making it easier for users to diagnose heart disease. The heart sound is obtained from the mechanical activity of the heart which is tapped by a condenser mic. The heart sound will be held in a pre-amp circuit, then the filters used are High Pass Filters and Low Pass Filters with an interrupted frequency of 20-95 Hz. The output of the filter circuit will enter the booster circuit. Then it will be processed by the microcontroller. In processing the data that will be displayed on Nextion and Speaker, the author uses Arduino Mega. Based on the test, it can be seen that the digital filter has a slight error rate because it removes the most noise, while in the analog filter there is still a lot of noise. The results of the research that has been done can be implemented using a system that really supports the needs.